Interpretation Of Oil Price Shocks On Macroeconomic Aggregates Of South Africa: Evidence From SVAR - Yıldız, Bünyamin Fuat; Hesami, Siamand; Rjoub, Husam; Wong, Wing-Keung (The journal of contemporary issues in business and government, 2021)
The effect of oil prices on macroeconomic aggregates has always been interesting. The recent decline in oil prices has highlighted the effects of oil price shocks both in supply and demand perspective. This study investigates the impact of the oil price shocks on the South African economy using a structural Vector Autoregressive (VAR) model offered by Peersman (2005). The model was established following the economic theory, considering the short and long-term constraints—and widely cited but rarely applied in the literature.This study shows no significant effect from supply and demand shocks to the oil prices in the short-run. Furthermore, monetary policy shocks have no immediate effect on output, and demand shock has no persistent impact on GDP. An interesting result is that oil price shocks have a limited positive effect on output. The reason for this is the high density of alternative carbon-based energy sources unique to South Africa. Finally, the monetary policy shock has an impact on all variables except for output. This study's results highlight the importance of understanding the oil price movements' source since oil price shocks necessarily do not imply a positive effect on the economy. Another result of the study emphasizes the importance of inflation stabilization and the importance of managing economies' supply-side.